Isolation of Prebiotics from Artocarpus integer’s Seed - Joel-Ching-Jue Wong; Siew-Ling Hii; Chen-Chung Koh (International Journal of Food Science)
There has been a high amount of attention given to prebiotics due to their significant physiological function and health benefits. Prebiotics contain nondigestible compounds that allow specific changes, both in the growth and in the activity of bacteria in the host gastrointestinal tract, that provide benefits upon the host by promoting a healthy digestive system and preventing disease. This study aims at investigating the potential prebiotic activity of bioactive compounds extracted from the seeds of an underutilized indigenous plant Artocarpus integer (A. integer). The optimum microwave-assisted extraction conditions were a microwave power of 1500 W, extraction time of 180 s, and solvent-to-sample ratio of 1000 : 1. The maximum amount of the total carbohydrate content extracted from A. integer was 787 mg/L. The percentage hydrolysis levels of A. integer extract in gastric juice at pH 1, 2, 3, and 4 were 6.14%, 7.12%, 8.98%, and 10.23%, respectively. For enzymatic digestion, the percentage of hydrolysis was 0.16% at pH 7. A. integer extract was found to support the growth of probiotics such as L. acidophilus and L. casei. After 72 hours of incubation, L. acidophilus achieved 6.96 log10 CFU, whereas L. casei reached 8.33 log10 CFU. The study makes an important contribution to the development of the use of Sarawakian underutilized plants and to the identification of new sources of prebiotic materials to be used in food.